Correction: Zhang et al. Interactions of Self-Assembled Bletilla Striata Polysaccharide Nanoparticles with Bovine Serum Albumin and Biodistribution of Its Docetaxel-Loaded Nanoparticles. Pharmaceutics 2019, 11, 43 - Guangyuan Zhang; Jin Qiao; Xin Liu; Yuran Liu; Ji Wu; Long Huang; Danyang Ji; Qingxiang Guan (Pharmaceutics)
In the original publication [...]